2015
DOI: 10.1165/rcmb.2014-0474oc
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Sirtuin 1–Mediated Control of Circadian Molecular Clock and Inflammation in Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is the fourth most common cause of death, and it is characterized by abnormal inflammation and lung function decline. Although the circadian molecular clock regulates inflammatory responses, there is no information available regarding the impact of COPD on lung molecular clock function and its regulation by sirtuin 1 (SIRT1). We hypothesize that the molecular clock in the lungs is disrupted, leading to increased inflammatory responses in smokers and patients with CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 51 publications
4
66
1
Order By: Relevance
“…We have shown that environmental CS exposure also causes circadian disruption, producing molecular clock dysfunction and enhanced inflammatory responses in the lungs (10). Abundance of clock proteins, such as BMAL1, PER2, and REV-ERBa, are reduced in peripheral blood mononuclear cells, sputum cells and lung tissues associated with inflammatory responses from smokers and patients with COPD when compared to nonsmokers (24). Hence, it is likely that the molecular clock dysfunction can augment lung inflammatory responses to environmental stressors/agents.…”
Section: Virus and Bacteriamentioning
confidence: 95%
See 2 more Smart Citations
“…We have shown that environmental CS exposure also causes circadian disruption, producing molecular clock dysfunction and enhanced inflammatory responses in the lungs (10). Abundance of clock proteins, such as BMAL1, PER2, and REV-ERBa, are reduced in peripheral blood mononuclear cells, sputum cells and lung tissues associated with inflammatory responses from smokers and patients with COPD when compared to nonsmokers (24). Hence, it is likely that the molecular clock dysfunction can augment lung inflammatory responses to environmental stressors/agents.…”
Section: Virus and Bacteriamentioning
confidence: 95%
“…It is possible that oxidative/carbonyl stress (CS)-mediated reduction of SIRT1 level/activity leads to hyperacetylation of clock proteins and/or clock gene-associated histones, culminating in abnormal rhythms of proinflammatory and molecular clock gene expression. Indeed, we have shown that molecular clock dysfunction, along with SIRT1 reduction, contributes to abnormal inflammatory responses in smokers and patients with COPD (24). SIRT1 activation reduces CS-induced acetylation and degradation of BMAL1 in mouse lungs.…”
Section: Sirtuin 1 and Clock Protein Deacetylation During Inflammatiomentioning
confidence: 95%
See 1 more Smart Citation
“…Similar to asthma, the diurnal variation in symptom severity has been observed during COPD exacerbations, with elevated risk for intubation during early morning hours in the emergency department (82). Exciting research is emerging showing environmental risks of COPD, such as tobacco smoking, can affect components of the circadian clock (83), which may lead to chronic inflammatory responses (84). As future studies elucidate the interrelationship between circadian rhythm and COPD, new therapeutic targets and approaches may emerge in COPD treatment.…”
Section: Circadian Rhythm In Copdmentioning
confidence: 99%
“…Cigarette smoking led to decreased Sirtuin-1 activity leading to altered Bmal I: Clock activity (12). This finding may be a contributing factor for increased inflammation seen in smokers with COPD (13).…”
mentioning
confidence: 98%